A poststructuralist-informed inclusive masculinity theory (PS-IMT): developing IMT to account for complexities in masculinities, using learning to dance Latin and ballroom as an example. Issue 5 (3rd July 2020) - Owen, Craig; Riley, Sarah
ABSTRACT: Inclusive Masculinity Theory (IMT) offers an important framework for conceptualizing masculinities within cultures characterized by declining homophobia. But the framework faces several challenges when it theorizes masculinities as relatively stable sets of attitudes and behaviours in the context of complex and dynamic contemporary gender practices and identifications. Offering a solution through a poststructuralist-informed IMT (PS-IMT), we reconceptualize orthodox and inclusive masculinities as discourses that produce subject positions, which may require individuals to work on themselves ('technologies of self') to inhabit. Applying PS-IMT to data from a four-year ethnography with young men in a Latin and ballroom UK university dance society, an analysis of the problematic of 'stiff hips' is playfully presented as a set of dance steps. Step one shows stiff hip movements embodying orthodox masculinity; step two, an entanglement of orthodox and inclusive masculinities as participants work to loosen their hip movement, enabling immersion in inclusive masculinity in step three; while step four evidenced a reframing of fluid hip movements into a new form of orthodox masculinity. Through these steps we chart complex, dynamic shifts across the fault lines of orthodox and inclusive masculinities, illustrating how PS-IMT offers important directions for masculinities research.